Prevalence of Post Traumatic Stress Disorder Among Secondary School Students in Baquba - J Hmmod, Hayder (Diyala Journal of Medicine, 2019)
Background: Post traumatic stress disorder occurs at high rate in adolescents and its rate appears to be rising . because this syndrome can have long lasting effect when it occurs before adulthood ,early recognition and treatment are vital . Aims of the study: This study aims to identify the life time prevalence rate of PTSD among secondary school student and the relation of socio demographic characteristics after students exposed to stressful evens in their life Baquba city. which is considered to be one of the hot areas in Iraq . Method: 296 secondary schools students were selected randomly from six secondary schools in Baquba city for the period from 1/10/2005 to 25/12/2005 those student were screened by semi-structure interview based on (DSM IV) criteria for the diagnosis of PTSD . Results: The rate of life – time prevalence of PTSD among those students was 27.4% and the rate was higher among female which is 31% mainly of 13-14 years old and 24.6% in males mainly of 12-13 years old also the study revealed that the rate was higher in low socio economic stat and also high in students who live in urban area and those with family loss and injury . Conclusion: The life-time prevalence of PTSD in adolescents (12-18) years of age is relatively high and it is higher in female than male and the rate is high